Bimbingan Belajar terhadap Anak Speech Delay - Sri Ayu Laali; Hasna Kobaa; Windi I Kile; Maspa Djibran; Sujini M Mutalib; Amelia Amelia (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The development of language skills in children is an important factor in their growth. However, not all children experience language development appropriate for their age, one of which is speech delay. This study aims to analyze the factors that influence speech delay in children at RA Nurul Iman School, Beringin Jaya Village. The method used was direct observation of children experiencing speech delay, along with the delivery of educational materials to parents and teachers regarding the importance of verbal stimulation and the regulation of gadget usage. The research results show that the main factors causing speech delay in children at this school are excessive use of gadgets and a lack of verbal stimulation from parents. The study concludes that regulating gadget usage and increasing verbal stimulation from parents can help address speech delay issues in children and support their language development optimally. Therefore, it is important to raise awareness among parents about their role in supporting their children's speech development